Highly adhesive comb-branched polymer and its synthesis method and application

A highly adhesive comb-like branched polymer was synthesized by anionic active polymerization, which solved the problem of insufficient adhesive properties of existing branched polymers and achieved high adhesion and low-cost industrial production. It is suitable for enhancing the adhesion between rubber and steel cord.

CN116410424BActive Publication Date: 2025-03-11PETROCHINA CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111635687.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-29
Publication Date
2025-03-11
Estimated Expiration
2041-12-29

AI Technical Summary

Technical Problem

Existing branched polymers have shortcomings in adhesive properties, especially in the adhesion between rubber and steel cord, which affects driving safety. Furthermore, the synthesis methods of branched polymers are complex and costly, making them difficult to apply industrially.

Method used

A highly adhesive comb-like branched polymer was synthesized by using anionic living polymerization and controlling the amount of anionic monomers and initiators added. This process involved using 2,2-bis(2-furanyl)propane as a structure modifier under anhydrous and oxygen-free conditions, adding epoxide and styrene compounds containing halogens, and then adding a terminator and an antioxidant to prepare a comb-like branched polymer with excellent adhesive properties.

Benefits of technology

The synthesis of highly adhesive comb-like branched polymers has been achieved, which have excellent adhesive properties, are simple to operate, low in cost, and easy to industrialize. They significantly improve the bonding performance between objects, especially the adhesion between rubber and steel wire cord.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116410424B_ABST
    Figure CN116410424B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polymer materials, and is a high-adhesive comb-shaped branched polymer and a synthesis method and application thereof. The high-adhesive comb-shaped branched polymer is obtained according to the following method: firstly, an anionic polymerization technology is used to synthesize a polymer active chain, which is sequentially reacted with an alkylene oxide and a halogen-containing styrene compound to prepare a macromolecular monomer containing a styrene structure, and an anionic reaction monomer is continuously added, and polymerization is initiated again with n-butyl lithium. The high-adhesive comb-shaped branched polymer synthesized by the invention has excellent adhesion performance, and the synthesis method thereof is simple to operate, has low synthesis cost, is convenient for industrial production, and can be used in plastic or rubber blending, which is beneficial to improving the adhesion performance of the polymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and relates to a high-adhesive comb-shaped branched polymer and a synthesis method and application thereof. Background Art

[0002] Tackiness is one of the important properties of polymers. There are many places in life that involve polymer tackiness. Among them, a typical example is pressure-sensitive adhesive (full name pressure-sensitive adhesive), which is widely used in office supplies, medical processing, packaging industry and daily necessities. In addition, the main component of tires is rubber. Rubber alone cannot withstand too much pressure. The pressure that tires withstand mainly depends on the adhesion between rubber and steel wire. If there is an adhesion defect between rubber and steel cord, it will directly affect the safety of drivers and vehicles and cargo. It is extremely important to ensure good adhesion between rubber and steel wire.

[0003] Compared with linear polymers, branched polymers have lower intrinsic viscosity, higher glass transition temperature and stronger adhesion behavior. Among them, branched polymers often use linear polymers as the skeleton, and multiple branched structures are randomly distributed on the skeleton to form different branched structures. The viscoelastic properties of this type of polymer are often very complex, involving factors such as the molecular weight, molecular weight distribution, number of branching points, branching density and distribution of branched structures along the main chain or other branches of the main chain and branched structures. Each branched structure is connected by multiple branching points, and the typical feature is that the relaxation process is hierarchical, that is, the branched structure is relaxed first, and then the main chain is relaxed. The rheological properties of branched polymers with special structures are often affected by long branched chain structures, and have significant linear and nonlinear rheological properties, such as graded relaxation, easy strain hardening under low elongation, etc. Therefore, the development of branched polymers in adhesive behavior plays a vital role in its industrial production and application. Summary of the invention

[0004] The present invention provides a high-adhesion comb-branched polymer and a synthesis method and application thereof, which overcome the deficiencies of the above-mentioned prior art. The synthesized high-adhesion comb-branched polymer has excellent adhesion performance, and the synthesis method thereof is simple to operate, has low synthesis cost, and is convenient for industrial production.

[0005] One of the technical solutions of the present invention is achieved by the following measures: a high-adhesive comb-branched polymer is obtained by the following method:

[0006] The first step is to prepare a polymer active chain by using 2,2-di(2-furyl)propane as a structure regulator in an organic solvent under anhydrous and oxygen-free conditions, adding anionic polymerization monomers, and initiating polymerization with an initiator, wherein 0.001 mmol to 50.000 mmol of initiator is added per milliliter of anionic polymerization monomer, and the molar ratio between the structure regulator and the initiator is 1:2;

[0007] The second step is to sequentially add alkylene oxide and halogen-containing styrene compound to the polymer active chain to prepare a macromonomer containing a styrene structure, and then continue to add anionic polymerization monomers, and initiate again with an initiator to prepare a polymerization product, wherein the molar ratio of alkylene oxide to the polymer active chain is 0.5 to 1.5:1, the molar ratio of the halogen-containing styrene compound to the polymer active chain is 0.5 to 1.5:1, and 0.001 mmol to 50.000 mmol of initiator is added per milliliter of anionic polymerization monomer;

[0008] The third step is to add a terminator and an antioxidant to the polymerization product to terminate the reaction, and then successively carry out precipitation washing, filtration and vacuum drying to obtain a comb-like branched polymer.

[0009] The following is a further optimization and / or improvement of one of the above-mentioned technical solutions:

[0010] The initiator is one of alkyl lithium, alkali metal alkoxide and sodium naphthalene; the alkyl lithium is one of isopropyl lithium, n-butyl lithium, sec-butyl lithium and tert-butyl lithium; the alkali metal alkoxide is lithium cycloheximide; the anionic polymerization monomer is one of isoprene, butadiene, styrene, methyl styrene and methyl methacrylate; and the organic solvent is one of n-hexane, n-pentane, cyclopentane and tetrahydrofuran.

[0011] The above-mentioned alkylene oxide is one of ethylene oxide and propylene oxide; the styrene compound containing halogen element is one of p-chloromethylstyrene, 3-chlorostyrene, 2-bromostyrene, 4-bromo-trans-stilbene, divinylbenzene, 4-bromostyrene and 2-chlorostyrene.

[0012] The above-mentioned terminator is one of carbon dioxide, organic acid and water; the antioxidant is one of 2,6-di-tert-butyl-4-methylphenol, 2,6-di-tert-butylphenol, 2,2-methylenebis(4-methyl-6-tert-butylphenol), 2,6-di-tert-butyl-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol and tris(2,4-di-tert-butyl)phenyl phosphite.

[0013] The molar ratio of the above-mentioned alkylene oxide to the active chain of the polymer is 0.9 to 1.1:1; the molar ratio of the halogen-containing styrene compound to the active chain of the polymer is 0.9 to 1.1:1.

[0014] The concentration of the above-mentioned initiator is 0.1 mol / L to 10.0 mol / L; in the first step, during polymerization, the reaction temperature is 20°C to 90°C, the reaction time is 1min to 400min, and the solid content of the anionic polymerization monomer does not exceed 50%.

[0015] Preferably, the initiator concentration is 0.5 mol / L to 2.0 mol / L; in the first step, during polymerization, the reaction temperature is 30° C. to 70° C., and the solid content of the anionic polymerization monomer is 15%.

[0016] The second technical solution of the present invention is achieved by the following measures: A method for synthesizing a high-adhesive comb-branched polymer is carried out as follows:

[0017] The first step is to prepare a polymer active chain by using 2,2-di(2-furyl)propane as a structure regulator in an organic solvent under anhydrous and oxygen-free conditions, adding anionic polymerization monomers, and initiating polymerization with an initiator, wherein 0.001 mmol to 50.000 mmol of initiator is added per milliliter of anionic polymerization monomer, and the molar ratio between the structure regulator and the initiator is 1:2;

[0018] The second step is to sequentially add alkylene oxide and halogen-containing styrene compound to the polymer active chain to prepare a macromonomer containing a styrene structure, and then continue to add anionic polymerization monomers, and initiate again with an initiator to prepare a polymerization product, wherein the molar ratio of alkylene oxide to the polymer active chain is 0.5 to 1.5:1, the molar ratio of the halogen-containing styrene compound to the polymer active chain is 0.5 to 1.5:1, and 0.001 mmol to 50.000 mmol of initiator is added per milliliter of anionic polymerization monomer;

[0019] The third step is to add a terminator and an antioxidant to the polymerization product to terminate the reaction, and then successively carry out precipitation washing, filtration and vacuum drying to obtain a comb-like branched polymer.

[0020] The following is a further optimization and / or improvement of the second technical solution of the above invention:

[0021] The initiator is one of alkyl lithium, alkali metal alkoxide and sodium naphthalene; the alkyl lithium is one of isopropyl lithium, n-butyl lithium, sec-butyl lithium and tert-butyl lithium; the alkali metal alkoxide is lithium cycloheximide; the anionic polymerization monomer is one of isoprene, butadiene, styrene, methyl styrene and methyl methacrylate; and the organic solvent is one of n-hexane, n-pentane, cyclopentane and tetrahydrofuran.

[0022] The above-mentioned alkylene oxide is one of ethylene oxide and propylene oxide; the styrene compound containing halogen element is one of p-chloromethylstyrene, 3-chlorostyrene, 2-bromostyrene, 4-bromo-trans-stilbene, divinylbenzene, 4-bromostyrene and 2-chlorostyrene.

[0023] The above-mentioned terminator is one of carbon dioxide, organic acid and water; the antioxidant is one of 2,6-di-tert-butyl-4-methylphenol, 2,6-di-tert-butylphenol, 2,2-methylenebis(4-methyl-6-tert-butylphenol), 2,6-di-tert-butyl-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol and tris(2,4-di-tert-butyl)phenyl phosphite.

[0024] The molar ratio of the above-mentioned alkylene oxide to the active chain of the polymer is 0.9 to 1.1:1; the molar ratio of the halogen-containing styrene compound to the active chain of the polymer is 0.9 to 1.1:1.

[0025] The concentration of the above-mentioned initiator is 0.1 mol / L to 10.0 mol / L; in the first step, during polymerization, the reaction temperature is 20°C to 90°C, the reaction time is 1min to 400min, and the solid content of the anionic polymerization monomer does not exceed 50%.

[0026] Preferably, the initiator concentration is 0.5 mol / L to 2.0 mol / L; in the first step, during polymerization, the reaction temperature is 30° C. to 70° C., and the solid content of the anionic polymerization monomer is 15%.

[0027] The third technical solution of the present invention is achieved through the following measures: application of a high-adhesion comb-branched polymer in a high-adhesion polymer material.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The present invention adopts anionic living polymerization, and by controlling the amount of anionic polymerization monomer and initiator added, different types of comb-branched polymers can be prepared, and different degrees of adhesive performance improvement can be achieved. At the same time, the synthesis method of the high-adhesion comb-branched polymer of the present invention has the characteristics of mild reaction conditions, simple operation, and low production cost, and has good industrial value. It can be directly used or added to other polymers, and can significantly improve the bonding performance between objects.

[0030] The high-adhesive comb-branched polymer synthesized by the invention has excellent adhesive properties, and its synthesis method is simple to operate, low in synthesis cost, and convenient for industrial production. At the same time, it can be used in plastic or rubber blending, which is beneficial to improving the adhesive properties of the polymer. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1Schematic diagram of the synthesis route of the high-adhesive comb-branched polymer of the present invention.

[0032] Figure 2 This is the nuclear magnetic resonance spectrum of the branched polymer I prepared in Example 8 of the present invention.

[0033] Figure 3 This is a rheological frequency scan diagram of the branched polymer I prepared in Example 8 of the present invention.

[0034] Figure 4 This is a graph showing the adhesion performance of branched polymer I prepared in Example 8 of the present invention.

[0035] Figure 5 This is a structural diagram of branched polymer I prepared in Example 8 of the present invention.

[0036] Figure 6 This is a rheological frequency scanning diagram of the branched polymer II prepared in Example 9 of the present invention.

[0037] Figure 7 This is a structural diagram of the branched polymer II prepared in Example 9 of the present invention.

[0038] Figure 8 This is a rheological frequency scanning diagram of the branched polymer III prepared in Example 10 of the present invention. DETAILED DESCRIPTION

[0039] The present invention is not limited by the following embodiments, and the specific implementation method can be determined according to the technical scheme of the present invention and the actual situation. Unless otherwise specified, the various chemical reagents and chemicals mentioned in the present invention are all chemical reagents and chemicals known and used in the prior art; unless otherwise specified, the percentages in the present invention are all mass percentages; unless otherwise specified, the solutions in the present invention are all aqueous solutions with water as the solvent, for example, hydrochloric acid solution is a hydrochloric acid aqueous solution; the normal temperature and room temperature in the present invention generally refer to a temperature of 15°C to 25°C, and are generally defined as 25°C.

[0040] The present invention will be further described below in conjunction with embodiments:

[0041] Example 1: The high-adhesive comb-branched polymer is obtained by the following method:

[0042] The first step is to prepare a polymer active chain by using 2,2-di(2-furyl)propane as a structure regulator in an organic solvent under anhydrous and oxygen-free conditions, adding anionic polymerization monomers, and initiating polymerization with an initiator, wherein 0.001 mmol to 50.000 mmol of initiator is added per milliliter of anionic polymerization monomer, and the molar ratio between the structure regulator and the initiator is 1:2;

[0043] The second step is to sequentially add alkylene oxide and halogen-containing styrene compound to the polymer active chain to prepare a macromonomer containing a styrene structure, and then continue to add anionic polymerization monomers, and initiate again with an initiator to prepare a polymerization product, wherein the molar ratio of alkylene oxide to the polymer active chain is 0.5 to 1.5:1, the molar ratio of the halogen-containing styrene compound to the polymer active chain is 0.5 to 1.5:1, and 0.001 mmol to 50.000 mmol of initiator is added per milliliter of anionic polymerization monomer;

[0044] The third step is to add a terminator and an antioxidant to the polymerization product to terminate the reaction, and then successively carry out precipitation washing, filtration and vacuum drying to obtain a comb-like branched polymer.

[0045] Example 2: As an optimization of the above-mentioned Example 1, the initiator is one of alkyl lithium, alkali metal alkoxide and sodium naphthalene, the alkyl lithium is one of isopropyl lithium, n-butyl lithium, sec-butyl lithium and tert-butyl lithium, and the alkali metal alkoxide is lithium cycloheximide; the anionic polymerization monomer is one of isoprene, butadiene, styrene, methyl styrene and methyl methacrylate; the organic solvent is one of n-hexane, n-pentane, cyclopentane and tetrahydrofuran.

[0046] Example 3: As an optimization of the above Example 1, the alkylene oxide is one of ethylene oxide and propylene oxide; the styrene compound containing halogen elements is one of p-chloromethylstyrene, 3-chlorostyrene, 2-bromostyrene, 4-bromo-trans-stilbene, divinylbenzene, 4-bromostyrene and 2-chlorostyrene.

[0047] Example 4: As an optimization of the above Example 1, the terminator is one of carbon dioxide, organic acid and water; the antioxidant is one of 2,6-di-tert-butyl-4-methylphenol, 2,6 di-tert-butylphenol, 2,2-methylenebis(4-methyl-6-tert-butylphenol), 2,6-di-tert-butyl-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol, and tris(2,4-di-tert-butyl)phenyl phosphite.

[0048] Example 5: As an optimization of the above Example 1, the molar ratio of alkylene oxide to polymer active chain is 0.9 to 1.1:1, and the molar ratio of halogen-containing styrene compound to polymer active chain is 0.9 to 1.1:1.

[0049] Example 6: As an optimization of the above Example 1, the concentration of the initiator is 0.1 mol / L to 10.0 mol / L; in the first step, during polymerization, the reaction temperature is 20°C to 90°C, the reaction time is 1 min to 400 min, and the solid content of the anionic polymerization monomer does not exceed 50%. This is because as the solid content of the monomer in the reaction solution increases, the danger caused by the thermal effect of the polymerization reaction becomes greater.

[0050] Example 7: As an optimization of the above Example 6, the initiator concentration is 0.5 mol / L to 2.0 mol / L; in the first step, during polymerization, the reaction temperature is 30°C to 70°C, and the solid content of the anionic polymerization monomer is 15%.

[0051] The present invention does not limit the terminator and the antioxidant, and they can be determined according to the conventional dosage added in the current branched polymer preparation process.

[0052] The present invention first adopts anionic polymerization technology, reacts the synthesized polymer active chain with alkylene oxide, and then reacts with a halogen-containing styrene compound to smoothly synthesize a macromolecular chain containing a styrene structure, continues to add anionic polymerization monomers, and initiates polymerization with an initiator again to synthesize a high-adhesion comb-shaped branched polymer. Wherein, the branched structure can be polyisoprene, polybutadiene, polybutylene styrene, etc., and its molecular weight can be 10 kg / mol to 300 kg / mol, and the number of branches can be 3 to 100. The synthetic method of the high-adhesion comb-shaped branched polymer of the present invention is simple to operate, has low synthesis cost, and is convenient for industrial production. The high-adhesion comb-shaped branched polymer of the present invention has preferably adhesive properties, can be used in plastics or rubber blends, increases the adhesive properties of polymers, improves the bonding between polymers or between polymers and other objects, such as can be used to solve the bonding enhancement between each layer of tire rubber or between a rubber layer and a steel wire.

[0053] Example 8: According to Figure 1Schematic diagram of the synthesis route, wherein n-BuLi is butyl lithium; OOPS is a structural regulator 2,2-di(2-furyl)propane. The highly adhesive comb-branched polymer is obtained by the following method: first, 20 ml of anionic polymerization monomer isoprene is added to 400 ml of n-hexane solution, and polymerization is initiated with 1.70 ml of n-butyl lithium (molar concentration is 1 mmol / ml) under the action of the structural regulator 2,2-di(2-furyl)propane OOPS (the molar ratio of the structural regulator to the initiator is 1:2), and the reaction is carried out in a 60°C water bath for 2 hours. After cooling to room temperature, a polymer active chain is obtained; propylene oxide is added to the polymer active chain in an amount 1.1 times the molar number of the polymer active chain, and the reaction is carried out for 1 hour to transfer the active center to the oxygen atom, and then p-chloromethylstyrene is added in an amount equimolar to the polymer active chain to obtain a polymer long chain containing double bonds (the active center is transferred to the oxygen atom, which can avoid the active center from directly reacting with the double bond of p-chloromethylstyrene). 40 ml of isoprene monomer was added to the reaction system of the polymer long chain containing double bonds, and 1.02 ml of n-butyl lithium (molar concentration of 1 mmol / ml) was used again to initiate polymerization. The polymerization temperature was 60°C and the reaction was carried out for 2 hours to obtain a polymer product. After the polymerization reaction was completed, water and 2,6-di-tert-butyl-4-methylphenol were added to the polymer product to terminate the reaction. After washing, filtering and vacuum drying, a comb-like branched polymer (hereinafter referred to as branched polymer I) was obtained.

[0054] The molecular weight of the branched polymer I prepared in Example 8 of the present invention was measured by a gel permeation chromatograph (GPC) of Malvern Company. The weight average molecular weight of the branched polymer I was 44100, and the polydispersity M w / M n The molecular weight of the branched structure is 1.14, the branching degree is 2.5, and the purity is 90.3%.

[0055] The microstructure of the branched polymer I was analyzed by nuclear magnetic resonance (see Figure 2 ), the branched polymer I has a 1,2-structure polyisoprene content of 5.60%, a 3,4-structure polyisoprene content of 64.68%, a cis-1,4-polyisoprene structure content of 17.90%, and a trans-1,4-polyisoprene structure content of 11.82%.

[0056] The branched polymer I was subjected to rheological frequency scanning, the test thickness was 1 mm, and the sample was scanned in the frequency range of 0.01 Hz to 100 Hz using a 25 mm plate (see Figure 3 ).

[0057] The adhesion performance test of the branched polymer I was carried out by using a stainless steel probe adhesion test method (probe diameter 12 mm, surface roughness Ra 0.12 um, sample thickness 1 mm). The probe pressed the sample down to -5 N at a speed of 0.01 mm / s. After a sufficiently long relaxation time, the adhesion performance was tested at different separation speeds. The relationship between the maximum separation force of the probe and the separation speed at different separation speeds (see Figure 4 ),from Figure 4 It can be seen that when the probe separation speed is 5 mm / s, the maximum separation force during the separation process is as high as 59 N.

[0058] The branched polymer I structure (see Figure 5 ), the branched polymer I is comb-like.

[0059] Comparative Example 1: 60 ml of isoprene monomer was added to 400 ml of n-hexane solution, and polymerization was initiated with 1.00 ml of n-butyl lithium (molar concentration of 1 mmol / ml), and the reaction was carried out in a 60°C water bath for 2 hours. After the reaction was completed, linear polyisoprene was obtained by precipitation washing, filtration, vacuum drying, etc. The molecular weight of the linear polyisoprene obtained in Comparative Example 1 of the present invention was measured by a gel permeation chromatograph (GPC) of Malvern Company. The weight average molecular weight of the linear polyisoprene was 45031, and the polydispersity M w / M n The linear polyisoprene has low strength and is difficult to test for adhesion performance, and has very low adhesion.

[0060] Example 9: According to Figure 1A schematic diagram of the synthesis route of the high-adhesive comb-branched polymer is obtained by the following method: 20 ml of isoprene monomer is added to 400 ml of n-hexane solution, and polymerization is initiated with 1.70 ml of n-butyl lithium (molar concentration is 1 mmol / ml) under the action of a structure regulator 2,2-di(2-furyl)propane OOPS (the molar ratio of the structure regulator to the initiator is 1:2), and the reaction is carried out in a 60°C water bath for 2 hours, and the polymer active chain is obtained after cooling to room temperature; propylene oxide is added to the polymer active chain in an amount 1.1 times the molar number of the polymer active chain, and the reaction is carried out for 1 hour to transfer the active center to the oxygen atom, and then p-chloromethylstyrene is added in an amount equimolar to the polymer active chain to obtain a polymer long chain containing double bonds. 40 ml of isoprene monomer was added to the reaction system of the polymer long chain containing double bonds, and 0.51 ml of n-butyl lithium (molar concentration of 1 mmol / ml) was used again to initiate polymerization. The polymerization temperature was 60°C and the reaction was carried out for 2 hours to obtain a polymer product. After the polymerization reaction was completed, water and 2,6-di-tert-butyl-4-methylphenol were added to the polymer product to terminate the reaction. After washing, filtering, and vacuum drying, a comb-like branched polymer (hereinafter referred to as branched polymer II) was obtained.

[0061] The molecular weight of the branched polymer II prepared in Example 9 of the present invention was measured by a gel permeation chromatograph (GPC) of Malvern Company. The weight average molecular weight of the branched polymer II was 100700, and the polydispersity M w / M n The molecular weight of the branched structure is 1.31, the branching degree is 5400, and the purity is 94.4%.

[0062] The branched polymer II was subjected to rheological frequency scanning, with a test thickness of 1 mm and a 25 mm plate being used to scan the sample in a frequency range of 0.01 Hz to 100 Hz (see Figure 6 ), the branched polymer II also exhibits good adhesion properties and is very suitable for application in enhancing adhesion properties.

[0063] The adhesion performance test of the branched polymer II adopts the stainless steel probe adhesion test method (probe diameter is 12mm, surface roughness Ra is 0.12um, sample thickness is 1mm). The probe presses the sample to -5N at a speed of 0.01mm / s. After a sufficiently long relaxation time, its adhesion performance is tested at different separation speeds. When the probe separation speed is 5mm / s, the maximum separation force during the separation process is as high as 61N.

[0064] The branched polymer II structure (see Figure 7 ), the branched polymer II is comb-like.

[0065] Example 10: According to Figure 1 A schematic diagram of the synthesis route of the high-adhesive comb-branched polymer is obtained by the following method: 20 ml of isoprene monomer is added to 400 ml of n-hexane solution, and polymerization is initiated with 1.70 ml of n-butyl lithium (molar concentration is 1 mmol / ml) under the action of a structure regulator 2,2-di(2-furyl)propane OOPS (the molar ratio of the structure regulator to the initiator is 1:2), and the reaction is carried out in a 60°C water bath for 2 hours, and the polymer active chain is obtained after cooling to room temperature; propylene oxide is added to the polymer active chain in an amount 1.1 times the molar number of the polymer active chain, and the reaction is carried out for 1 hour to transfer the active center to the oxygen atom, and then p-chloromethylstyrene is added in an amount equimolar to the polymer active chain to obtain a polymer long chain containing double bonds. 40 ml of isoprene monomer was added to the reaction system of the polymer long chain containing double bonds, and 0.42 ml of n-butyl lithium (molar concentration of 1 mmol / ml) was used again to initiate polymerization. The polymerization temperature was 60°C and the reaction was carried out for 2 hours to obtain a polymer product. After the polymerization reaction was completed, water and 2,6-di-tert-butyl-4-methylphenol were added to the polymer product to terminate the reaction. After washing, filtering, and vacuum drying, a comb-like branched polymer (hereinafter referred to as branched polymer III) was obtained.

[0066] The molecular weight of the branched polymer III prepared in Example 10 of the present invention was measured by a gel permeation chromatograph (GPC) of Malvern Company. The weight average molecular weight of the branched polymer III was 100100, and the polydispersity M w / M n The molecular weight of the branched structure is 1.36, the degree of branching is 7.5, and the purity is 91.2%.

[0067] The microstructure of the branched polymer III was analyzed using a nuclear magnetic resonance instrument. The content of 1,2-structure polyisoprene in the branched polymer III was 7.38%, the content of 3,4-structure polyisoprene was 67.24%, the content of cis-1,4-polyisoprene structure was 16.46%, and the content of trans-1,4-polyisoprene structure was 8.91%.

[0068] The branched polymer III was subjected to rheological frequency scanning, with a test thickness of 1 mm and a 25 mm plate being used to scan the sample in a frequency range of 0.01 Hz to 100 Hz (see Figure 8 ), the branched polymer III also exhibits good adhesion properties and is very suitable for application in enhancing adhesion properties.

[0069] The adhesion performance test of the branched polymer III adopts the stainless steel probe adhesion test method (probe diameter is 12mm, surface roughness Ra is 0.12um, sample thickness is 1mm). The probe presses the sample to -5N at a speed of 0.01mm / s. After a sufficiently long relaxation time, its adhesion performance is tested at different separation speeds. When the probe separation speed is 5mm / s, the maximum separation force during the separation process is as high as 60N.

[0070] Comparative Example 2: 60 ml of isoprene monomer was added to 400 ml of n-hexane solution, and polymerization was initiated with 0.40 ml of n-butyl lithium (molar concentration of 1 mmol / ml), and the reaction was carried out in a 60°C water bath for 2 hours. After the reaction was completed, linear polyisoprene was obtained by precipitation washing, filtration, vacuum drying and other operations. The molecular weight of the linear polyisoprene obtained in Comparative Example 2 of the present invention was measured by a gel permeation chromatograph (GPC) of Malvern Company. The weight average molecular weight of the linear polyisoprene was 98900 and the polydispersity was 1.18. Using the same stainless steel probe adhesion test, when the separation speed was 5 mm / s, the maximum separation force in the linear polyisoprene separation process was only 43 N.

[0071] Example 11: According to Figure 1 Schematic diagram of the synthetic route of the invention. The highly adhesive comb-branched polymer is obtained by the following method: 4000 g of cyclopentane and 150 g of butadiene monomer are added to a 10 L reactor. Under the action of the structure regulator 2,2-di(2-furyl)propane OOPS (the molar ratio of the structure regulator to the initiator is 1:2), 20 mmol of n-butyl lithium is added to initiate polymerization. The entire reaction system is reacted at about 60°C for 2 hours with continuous stirring in the middle to obtain a polymer active chain. 1.05 times the molar number of propylene oxide as the polymer active chain is added to the polymer active chain, and the reaction is continued for 1 hour to transfer the active center to the oxygen atom. Subsequently, p-chloromethylstyrene is added in an amount equimolar to the polymer active chain to obtain a high molecular long chain containing double bonds. 300 g of butadiene monomer is added to the reaction system of the high molecular long chain containing double bonds, and polymerization is initiated again with 7.5 mmol of n-butyl lithium. After reacting for 2 hours, a highly adhesive comb-branched polymer (polybutadiene) is obtained. The high-adhesive comb-branched polymer can significantly improve the adhesive behavior of rubber.

[0072] In summary, the high-adhesion comb-branched polymer synthesized in the present invention has excellent adhesion performance, and its synthesis method is simple to operate, low in synthesis cost, and convenient for industrial production. At the same time, it can be used in plastic or rubber blending, which is beneficial to improving the adhesion performance of the polymer.

[0073] The above technical features constitute the embodiments of the present invention, which have strong adaptability and implementation effect. Non-essential technical features can be added or reduced according to actual needs to meet the requirements of different situations.

Claims

1. A high-adhesive comb-branched polymer, characterized in that Obtained as follows: The first step is to prepare a polymer active chain by using 2,2-di(2-furyl)propane as a structure regulator in an organic solvent, and initiating polymerization with an initiator under anhydrous and oxygen-free conditions, wherein 0.001 mmol to 50.000 mmol of initiator is added to each milliliter of anionic polymerization monomer, and the molar ratio between the structure regulator and the initiator is 1:2; the initiator is one of alkyl lithium, lithium cycloheximide and sodium naphthalene, and the alkyl lithium is one of isopropyl lithium, n-butyl lithium, sec-butyl lithium and tert-butyl lithium; the anionic polymerization monomer is one of isoprene and butadiene; and the organic solvent is one of n-hexane, n-pentane, cyclopentane and tetrahydrofuran; The second step is to sequentially add alkylene oxide and halogen-containing styrene compound to the polymer active chain to prepare a macromolecular monomer containing a styrene structure, and then continue to add anionic polymerization monomers, and initiate again with an initiator to prepare a polymerization product, wherein the molar ratio of alkylene oxide to the polymer active chain is 0.5 to 1.5:1, the molar ratio of the halogen-containing styrene compound to the polymer active chain is 0.5 to 1.5:1, and 0.001 mmol to 50.000 mmol of initiator is added per milliliter of anionic polymerization monomer; the alkylene oxide is one of ethylene oxide and propylene oxide, the halogen-containing styrene compound is one of p-chloromethylstyrene, 3-chlorostyrene, 2-bromostyrene, 4-bromo-trans-stilbene, 4-bromostyrene and 2-chlorostyrene; the anionic polymerization monomer is one of isoprene and butadiene; The third step is to add a terminator and an antioxidant to the polymerization product to terminate the reaction, and then successively carry out precipitation washing, filtration and vacuum drying to obtain a comb-like branched polymer.

2. The high-adhesive comb-branched polymer according to claim 1, characterized in that The terminator is one of carbon dioxide, organic acid and water; or / and, the antioxidant is one of 2,6-di-tert-butyl-4-methylphenol, 2,6-di-tert-butylphenol, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 4,6-bis(octylthiomethyl)-o-cresol, tris(2,4-di-tert-butyl)phenyl phosphite.

3. The high-adhesive comb-branched polymer according to claim 1 or 2, characterized in that The molar ratio of alkylene oxide to polymer active chain is 0.9 to 1.1:1, and the molar ratio of styrene compound containing halogen element to polymer active chain is 0.9 to 1.1:

1.

4. The high-adhesive comb-branched polymer according to claim 1 or 2, characterized in that The concentration of the initiator is 0.1 mol / L to 10.0 mol / L; or / and, in the first step, during polymerization, the reaction temperature is 20° C. to 90° C., the reaction time is 1 min to 400 min, and the solid content of the anionic polymerization monomer does not exceed 50%.

5. The high-adhesive comb-branched polymer according to claim 3, characterized in that The concentration of the initiator is 0.1 mol / L to 10.0 mol / L; or / and, in the first step, during polymerization, the reaction temperature is 20° C. to 90° C., the reaction time is 1 min to 400 min, and the solid content of the anionic polymerization monomer does not exceed 50%.

6. The high-adhesive comb-branched polymer according to claim 1, 2 or 5, characterized in that The initiator concentration is 0.5 mol / L to 2.0 mol / L; or / and, in the first step, during polymerization, the reaction temperature is 30° C. to 70° C., and the solid content of the anionic polymerization monomer is 15%.

7. A method for synthesizing the high-adhesive comb-branched polymer according to claim 1, 2 or 4, comprising: In the first step, under anhydrous and oxygen-free conditions, 2,2-di(2-furyl)propane is used as a structural regulator, anionic polymerization monomers are added to an organic solvent, and polymerization is initiated by an initiator to prepare a polymer active chain, wherein: 0.001 mmol to 50.000 mmol of initiator is added to each milliliter of anionic polymerization monomer, and the molar ratio between the structure regulator and the initiator is 1:2; The second step is to sequentially add alkylene oxide and halogen-containing styrene compound to the polymer active chain to prepare a macromonomer containing a styrene structure, and then continue to add anionic polymerization monomers, and initiate again with an initiator to prepare a polymerization product, wherein the molar ratio of alkylene oxide to the polymer active chain is 0.5 to 1.5:1, the molar ratio of the halogen-containing styrene compound to the polymer active chain is 0.5 to 1.5:1, and 0.001 mmol to 50.000 mmol of initiator is added per milliliter of anionic polymerization monomer; The third step is to add a terminator and an antioxidant to the polymerization product to terminate the reaction, and then successively carry out precipitation washing, filtration and vacuum drying to obtain a comb-like branched polymer.

8. Use of the high-adhesion comb-branched polymer according to any one of claims 1 to 6 in high-adhesion polymer materials.